Expectations of livestock sector from Union Budget in 2019-2020 - Jena, J (Indian Farming, 2019)
Livestock sector is an integral part of Indian agriculture and plays a critical role in the livelihood of rural population, serving as a source for food, more specifically protein for human diet, income and employment. For low-income household, livestock plays multifunctional roles as they serve as store of wealth and insurance mechanism for coping with household-related crisis, provide draught power and organic fertilizer for crop production and means of transport. Rising population, income growth and urbanization are fueling a world-wide change in dietary patterns in favour of livestock food products. This growth in developing country consumption of livestock food products is predicted to continue in the future. Per capita consumption of poultry meat, eggs and milk in India during the last few decades has registered a higher growth than that of pulse and cereal. The distinct increase in the demand for livestock food products not only contributes to nutritional security, but also provides income growth opportunities for rural poor and hence accelerates the pace of poverty reduction.